Quality of life of people living with HIV compared with that of the general population in Japan. Issue 10 (October 2017) - Hikasa, Shinichi; Shimabukuro, Shota; Hideta, Kyoko; Kuroda, Norihiro; Higasa, Satoshi; Sawada, Akihiro; Tokugawa, Tazuko; Ikegami, Asuka; Kotani, Asuna; Kimura, Takeshi
Abstract: Objective: To evaluate the health-related quality of life (HRQOL) of people living with HIV (PLWH) in Japan. Methods: A cross-sectional comparative study was conducted between June and December 2016 on PLWH. HRQOL was assessed using the Japanese version of the Short Form-36 Health Survey questionnaire (SF-36), and the three-component model of SF-36 scores was used. The values from the present study were compared with the published general Japanese values. Multivariate analysis was performed to identify the independent factors associated with the HRQOL of PLWH. Results: A total of 151 PLWH were enrolled in the present study. Six out of the eight subscales were significantly lower than the normative data. With respect to the summary scores, compared with those in the general population, the physical component summary score (PCS) was significantly higher in PLWH, although the mental and social/role component summary scores (MCS and RCS, respectively) were lower. Older Age was independently related to lower PCS; formal employment and higher CD4 counts were independently related to higher PCS. The factor associated with lower MCS was taking psychoactive drug(s). Formal employment was independently associated with higher RCS; taking psychoactive drug(s) was independently associated with lower RCS. Conclusions: The physical HRQOL of PLWH was slightly higher; however, the mental and social/role HRQOL were slightly lower than in the general population in Japan.